The Influence of Marketplace and Search Engine Optimization on Sales Volume at Fortunate Coffee CemaraAsri Thesis in 2023 - Ricardo, Frannico; Susanto (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2024)
This study entitled "The Effect of Marketplace and Search Engine Optimization on Sales Volume at Fortunate Coffee CemaraAsri". Lucky Coffee is a company engaged in the culinary field that provides a variety of healthy vegetarian foods. Lucky Coffee itself is located at JalanCemara Boulevard Utara Medan No. 8, CemaraAsri Complex, Deli Serdang. According to (Sumartini & Tias, 2019)sales volume is demand expressed quantitatively in terms of physical or volume or unit of a product. According to Opiida in (Kusumaningsih et al., 2021). Online marketplace is an internet-based online media that is used as a place for business transactions, where buyers can find as many sellers as possible according to market price criteria. In the Book (Enterprise, 2017)Search Engine Optimization is a way to increase a site's ranking in the list of search engine results. The method that the author uses is quantitative. The method that the author uses is quantitative. For research, the goal itself is to find out whether there is an effect of marketplace and search engine optimization on sales volume at Lucky Coffee CemaraAsri. The data used by the author is a questionnaire of 97 respondents for the sample taken. In the normality test on the Kolmogorov Smirnov column using the exact sig, it was found to be 0.07, which means that the data is normally distributed (> 0.05). The results of the multicollinearity test performed showed that the VIF obtained was 1.007 and also a tolerance of 0.993 means that multicollinearity does not occur (VIF <10 and tolerance > 0.1). The results of the heteroscedasticity test performed showed that Sig. the marketplace variable is 0.590 and search engine optimization is 0.073 so that in this study there is no heteroscedasticity problem (> 0.05). The test results for the coefficient of determination is 13.1%, which means that marketplace and search engine optimization have an influence on sales volume. The results of the multiple regression test are Y = 15.862 + 0.228 X1 + 0.305 X2. The results of the T test, the marketplace is 2.837 and search engine optimization is 2.642, where the ttable value is 1.985, tcount>ttable, then the marketplace and search engine optimization have an influence on sales volume. The result of fcount is 8.221 and ftable is 3.09 with a significance of 0.001. Thus, the independent variable has a significant effect simultaneously on the dependent variable.